2011
DOI: 10.1039/c0cp02461a
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation dynamics of the tert-butyl radical via photofragment translational spectroscopy at 248 nm

Abstract: The photodissociation dynamics of the tert-butyl radical (t-C(4)H(9)) were investigated using photofragment translational spectroscopy. The tert-butyl radical was produced from flash pyrolysis of azo-tert-butane and dissociated at 248 nm. Two distinct channels of approximately equal importance were identified: dissociation to H + 2-methylpropene, and CH(3) + dimethylcarbene. Neither the translational energy distributions that describe these two channels nor the product branching ratio are consistent with stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…This value is close to the one measured for the fast anisotropic component observed in the present experiments, with 1.34 eV at 250 nm and 1.40 eV at 255 nm excitation wavelength, respectively. The slow channel, on the other hand, was not reported by Negru et al 2 Most likely, this is due to the fact that the heavy fragment was monitored in their translational energy study. Its small deflection leads to a low sensitivity for slow H-atoms.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…This value is close to the one measured for the fast anisotropic component observed in the present experiments, with 1.34 eV at 250 nm and 1.40 eV at 255 nm excitation wavelength, respectively. The slow channel, on the other hand, was not reported by Negru et al 2 Most likely, this is due to the fact that the heavy fragment was monitored in their translational energy study. Its small deflection leads to a low sensitivity for slow H-atoms.…”
Section: Discussionmentioning
confidence: 83%
“…• Loss of a methyl group is an energetically possible pathway for all three alkyl radicals, but has yet only been observed for t-butyl. 2 Next, we will concentrate on the available data for t-butyl excited to the 3p state, because further information is available for comparison. Negru et al 2 identified two relevant channels in the photodissociation of t-butyl by translational energy spectroscopy using 248 nm excitation, H-loss and methyl-loss associated with dimethylcarbene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of this apparatus have been described previously. 50,[53][54][55] As in our previous investigation, 50 phenyl radicals were produced via flash pyrolysis of nitrosobenzene (Sigma, ≥97%) using a resistively heated SiC pyrolysis source based on the design by Kohn et al 51 The source was recently modified to include additional water cooling lines on the pulsed valve assembly and an aluminum heat shield around the SiC tube and electrodes, resulting in a significant increase in source stability and thus allowing for increased TOF integration times. A gas mixture of 1.6 atm of ∼10% N 2 in He was flowed over a room temperature sample of nitrosobenzene, resulting in a nitrosobenzene concentration of ∼0.5%, and was introduced into vacuum by expansion through a piezoelectric pulsed valve with the pyrolysis source attached.…”
Section: Methodsmentioning
confidence: 99%